2016
DOI: 10.1002/adfm.201504749
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic‐Field‐Directed Self‐Assembly of Programmable Mesoscale Shapes

Abstract: User‐programmed meso‐ to microscale 2D shapes using magnetic nanoparticles as building blocks with magnetic‐field‐directed self‐assembly are created. The assembly templates are magnetically recorded using perpendicular magnetic recording (PMR) media. The results demonstrate that PMR can template user‐designed features in two dimensions down to 30 nm in size, i.e., the nanoparticle diameter. It has been also shown that the nanoparticles assemble onto transitions between oppositely magnetized regions in the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…106,107 Self-assembly of nanoparticles can be achieved using various external stimuli such as temperature, 108 pH, 109 and the presence of biomolecules 110,111 and magnetic fields. 112 In self-assembled structures, a high level of order and intermolecular specific interactions are required. 106 …”
Section: Miscellaneous Phototriggered Drug Release Mechanismsmentioning
confidence: 99%
“…106,107 Self-assembly of nanoparticles can be achieved using various external stimuli such as temperature, 108 pH, 109 and the presence of biomolecules 110,111 and magnetic fields. 112 In self-assembled structures, a high level of order and intermolecular specific interactions are required. 106 …”
Section: Miscellaneous Phototriggered Drug Release Mechanismsmentioning
confidence: 99%
“…Such architectures are of interest for many applications, like drug delivery, bioanalysis, data and energy storage, sensors, and catalysis. [1][2][3][4][5][6][7][8][9][10] Recently, the magnetic field (MF)-assisted 11 self-assembly of magnetic colloids into organized nanostructures like fibers, chains, tubes, and circles [12][13][14] has attracted enormous attention. The studies demonstrated that a nanoscopic and mesoscopic orientational order can be achieved by application of an MF; however, the current strategies and the resulting assemblies do have specific stability aspects, which might be not compatible with some coveted applications.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the peak magnetic field gradient regions are located at the periphery of the protrusions [40][41][42]183]. For the deposition process, 0.2 ml of suspension is introduced on a 50 µm aluminum substrate, which is fixed on top of the patterned iron disc.…”
Section: Methodsmentioning
confidence: 99%
“…Magnetic manipulation of nanoparticles can be a promising approach to selectively deposit nanoparticles if the applied magnetic field is precisely modulated. Conventionally, magnetically directed surface-patterning has been limited to magnetic particles [40][41][42]. In this work, a novel approach has been demonstrated to manipulate not only magnetic particles but also a mixture of magnetic and nonmagnetic particles.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation